2015
DOI: 10.1007/s12020-015-0662-2
|View full text |Cite
|
Sign up to set email alerts
|

Levels of regulatory T cells CD69+NKG2D+IL-10+ are increased in patients with autoimmune thyroid disorders

Abstract: Regulatory T (Treg) cells play an important role in the pathogenesis of autoimmune thyroid disorders (AITD). New subsets of CD4(+)CD69(+) and CD4(+)NKG2D(+) T lymphocytes that behave as regulatory cells have been recently reported. The role of these immunoregulatory lymphocytes has not been previously explored in AITD. We analyzed by multi-parametric flow cytometry different Treg cell subsets in peripheral blood from 32 patients with AITD and 19 controls, and in thyroid tissue from seven patients. The suppress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
2
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 47 publications
0
34
2
2
Order By: Relevance
“…Thus, the aim of this study was to analyze the levels and function of CD69 + Treg cells in patients with PD. In this regard, we and others have recently described that although the frequency of these cells is low in peripheral blood, they seem to exert a relevant immune regulatory function, inhibiting the activation and proliferation of effector lymphocytes .…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Thus, the aim of this study was to analyze the levels and function of CD69 + Treg cells in patients with PD. In this regard, we and others have recently described that although the frequency of these cells is low in peripheral blood, they seem to exert a relevant immune regulatory function, inhibiting the activation and proliferation of effector lymphocytes .…”
Section: Discussionmentioning
confidence: 89%
“…Since we have previously observed that a subset of CD69 + Treg cells expresses the activation marker NKG2D , we decided to include this receptor in our flow cytometry analysis. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In murine models, lack of Treg aggravates the development of GD [8,35]. The thyroid of patients with GD is infiltrated with high proportion of Treg compared to autologous peripheral blood [36]. However, the role of Treg in GD pathogenesis remains to be elucidated in terms of Treg phenotype and function during the course of the disease and in terms of the plasticity of this subgroup of lymphocytes [37].…”
Section: Discussionmentioning
confidence: 99%
“…Since activated T cells stimulate B cells to proliferate and secrete antibodies (IgG), B cell tolerance mechanisms are considered as a secondary mechanism [13] . Tregs suppress immune responses against self or non-self Ags, producing immunosuppressive cytokines [interleukin-10 (IL-10), and transforming growth factor β (TGF-β)] and Tregs are dysfunctional in AITD patients [14,15] .…”
Section: Introductionmentioning
confidence: 99%